The Development of Learning Applications on Linear Equations Using A Contextual Approach - Putri, Desti Tatian; Susanti, Susanti; Astuti, Puji (Tarbiyah : Jurnal Ilmiah Kependidikan, 2024)
This research is motivated by limited learning media development to support students' learning processes. This research uses a contextual approach to test the validity and practicality of learning applications on linear equation material. The research method used is Research and Development (R&D), especially the 4D development model. To collect data, researchers used validation questionnaires distributed to experts in material, media, and language, as well as practicality instruments given to educators and students. The validation results show that the learning application on linear equation material using a contextual approach is very valid. The media expert assessment was 93.33%, the material expert assessment was 93.33%, and the language expert assessment was 92%. Then, the results of the practicality percentage obtained practical information with an assessment of the practicality of educators of 81.80% and an assessment of the practicality of students of 83.15%. Based on the overall data analysis results, the learning application developed is feasible and can be implemented in the learning process.